2022
DOI: 10.3390/jcm11175071
|View full text |Cite
|
Sign up to set email alerts
|

Complete Revascularization and One-Year Survival with Good Neurological Outcome in Patients Resuscitated from an Out-of-Hospital Cardiac Arrest

Abstract: Background. The survival benefit of complete versus infarct-related artery (IRA)-only revascularization during the index hospitalization in patients resuscitated from an out-of-hospital cardiac arrest (OHCA) with multivessel disease is unknown. Methods. We considered all the OHCA patients prospectively enrolled in the Lombardia Cardiac Arrest Registry (Lombardia CARe) from 1 January 2015 to 1 May 2021 who underwent coronary angiography (CAG) at the Fondazione IRCCS Policlinico San Matteo (Pavia). Patients’ pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
(50 reference statements)
0
1
0
Order By: Relevance
“…When it comes to patients after cardiac arrest there are no recommendations available on revascularization strategy in case of coronary multivessel disease. A recent retrospective study from our group [ 28 ] suggested that survival with good neurologic outcome of patients who received a complete revascularization, either during the index or staged procedure during the index hospitalization, was higher than the IRA-only group (83.3% vs. 30.4%, p 0.001). Even after correction for renal function, cardiac arrest duration, shockable rhythm, and the need for a pharmacologic or mechanical circulatory support a complete revascularization was confirmed to be independently associated with survival [HR 3 (95% CI 1.1–10), p = 0.04].…”
Section: Revascularization Strategy In Coronary Multivessel Diseasementioning
confidence: 99%
“…When it comes to patients after cardiac arrest there are no recommendations available on revascularization strategy in case of coronary multivessel disease. A recent retrospective study from our group [ 28 ] suggested that survival with good neurologic outcome of patients who received a complete revascularization, either during the index or staged procedure during the index hospitalization, was higher than the IRA-only group (83.3% vs. 30.4%, p 0.001). Even after correction for renal function, cardiac arrest duration, shockable rhythm, and the need for a pharmacologic or mechanical circulatory support a complete revascularization was confirmed to be independently associated with survival [HR 3 (95% CI 1.1–10), p = 0.04].…”
Section: Revascularization Strategy In Coronary Multivessel Diseasementioning
confidence: 99%